Gelatin-based biodegradable ureteral stents with enhanced mechanical properties. (December 2016) - Barros, Alexandre A.; Oliveira, Carlos; Lima, Estevão; Duarte, Ana Rita C.; Reis, Rui L.
Graphical abstract: Highlights: New gelatin-based biodegradable ureteral stents degrades in two weeks. Fully hydrogel stent with mechanical properties comparable with commercial ones. Stent degradation occurs in a homogenous away by slow dissolution. Preliminary in vivo study validated the enhanced mechanical properties. Preliminary in vivo study validated the surgical procedure. Abstract: A first generation of biodegradable ureteral stents based on natural origin polymers developed in a previous work has proven to be an interesting alternative to conventional stents, but it has however demonstrated to fail upon the first in vivo validation in a pig model. In this work, with the objective to overcome the low mechanical performance encountered and to make the biodegradable ureteral stents by origin polymers a success in vivo, four formulations with different concentrations of gelatin and alginate and different concentrations of crosslinking agent were tested in order to obtain higher mechanical properties. Bismuth was added to confer radiopaque properties to the stent. Not only a new formulation was developed but also the processing method to fabricate the stents was optimized. The biodegradable ureteral stents were coated with a biodegradable polymer. X-ray scan demonstrated the radiopacity of this second generation of biodegradable stents. The degradation of the biodegradable ureteral stents was assessed in artificial urine solution and it was observed that the degradation of the materials occurs in vitro between 9 and 15 days. Degradation was followed by weight loss of the samples and by chemical analysis of the solutions both by inductive couple plasma (ICP) and gel permeation chromatography (GPC). Formulation with highest amount of gelatin has shown good mechanical performance in terms of tensile properties when compared with the commercial stent (Biosoft ® duo, Porges, Coloplast), and the crosslinking concentration has shown not to have a great influence on the mechanical behavior of the stents. The in vivo performance of this second-generation of the ureteral stents was herein validated. The biodegradable ureteral stents were placed in the ureters of a female pig, following the normal surgical procedure. The animals remained asymptomatic, with normal urine flow, the stents remain intact during the first 3 days and after 10 days the ureteral stents were totally degraded. This new formulation combined with a new production process overcomes the problems verified with the first generation of natural-based biodegradable stents.